(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the author analyses the legal aspects of the right to privacy in the CIS countries and the Republic of Uzbekistan. The author points out that the concept of personal life is fixed at the level of the law to prevent different interpretations in practice and in the courts. The author believes that personal life is an area of human activity that relates exclusively to his personality, information about which a person tries to keep secret. The article concludes that freedom of thought, conscience and expression is also inextricably linked to the right to privacy. Everyone has the right to freedom of thought and expression of their beliefs, provided that this does not violate the rights and freedoms of others. Restrictions on these rights should be established only in cases provided for by law and be necessary in a democratic society.